PENYELESAIAN PEMUTUSAN HUBUNGAN KERJA TERHADAP DIREKTUR PERSEROAN YANG DAHULU BERSTATUS SEBAGAI PEKERJA PADA PERSEROAN YANG SAMA (Lex Jurnalica, 2019)
AbstractThe legal relationship between Worker/Labour and Entrepreneur is a subordinate working relationship based on the Employment Agreement between the parties. The economic and social position differences between Worker/Labour and Entrepreneur poses an unbalanced position. Therefore, in the industrial relations there is a government intervention as regulators or policymakers have an obligation to create a balanced industrial relationship among the interests of Worker/Labour, Entrepreneur, and governments. In the event of termination of employment which should be avoided and can only occur based on the agreement of the parties or the decision of the settlement institution of industrial relations dispute as stipulated in Law No. 3 of 2013 concerning Employment. While the legal relationship of Board of Directors and Board of Commissioners with the General Meeting of Shareholders (GMS) of a limited liability company is the civil law stipulated in the Law of the Republic of Indonesia No. 40 of 2007 concerning Limited Liability Company. The appointment and dismissal of a Member of the Board of Directors by the General Meeting of Shareholders (GMS) is as the fiduciary duty holder who is solely responsible for the management of the company for the purposes and objectives of the company and represents the company both inside and outside the court. Therefore, a Member of the Board of Directors is not the Worker/Labour or employee governed by the Law of the Republic of Indonesia No. 13 of 2003 concerning Employment. If a Worker/Labour or employee in a working relationship is appointed by the General Meeting of Shareholders (GMS) to be a Member of the Board of Directors/Commissioners, since the appointment, the legal status of the employee concerned, changed from an employment relationship (as a worker) to a (purely) civil relations, even though he/she is not a shareholder.Â Keywords: Termination, Company Director, Right ArisesÂ AbstrakHubungan hukum antara Pekerja/Buruh dengan Pengusaha adalah hubungan kerja yang bersifat subordinasi yang didasari oleh Perjanjian Kerja diantara para pihak. Perbedaan kedudukan secara ekonomi dan sosial antara pekerja/buruh dan pengusaha menimbulkan posisi yang tidak seimbang. Oleh karena itu di dalam hubungan industrial terdapat campur tangan Pemerintah sebagai regulator atau pembuat kebijakan mempunyai kewajiban untuk menciptakan hubungan industrial yang seimbang antara kepentingan pekerja/buruh, pengusaha, dan pemerintah. Dalam hal Pemutusan Hubungan Kerja, ini merupakan langkah yang harus dihindari dan hanya dapat terjadi atas kesepakatan para pihak atau putusan dari lembaga penyelesaian perselisihan hubungan industrial sebagaimana diatur dalam Undang-Undang Nomor 3 Tahun 2013 tentang Ketenagakerjaan. Sedangkan hubungan hukum Anggota Direksi dan Komisaris dengan Rapat Umum Pemegang Saham (RUPS) pada suatu Perseroan Terbatas adalah hubungan hukum perdata yang diatur dalam Undang-Undang Republik Indonesia Nomor 40 Tahun 2007 tentang Perseroan Terbatas. Pengangkatan dan pemberhentian seorang Anggota Direksi oleh Rapat Umum Pemegang Saham (RUPS) adalah sebagai pemegang amanat (fiduciary duty) yang bertanggung jawab penuh atas pengurusan Perseroan untuk kepentingan dan tujuan Perseroan dan mewakili Perseroan baik di dalam maupun di luar pengadilan. Dengan demikian, seorang anggota Direksi bukanlah Pekerja/Buruh atau karyawan yang diatur dalam Undang-Undang Republik Indonesia Nomor 13 Tahun 2003 tentang Ketenagakerjaan. Apabila seorang Pekerja/Buruh atau karyawan yang berada dalam hubungan kerja diangkat Rapat Umum Pemegang Saham (RUPS) menjadi Anggota Direksi/Komisaris, maka sejak pengangkatan tersebut, status hubungan hukum karyawan yang bersangkutan, berubah dari hubungan kerja (sebagai Pekerja) menjadi (murni) hubungan perdata, walaupun ia bukan Pemegang Saham.Â Kata Kunci: Pemutusan Hubungan Kerja, Direktur Persero, Muncul Hak